Advances in International Rice Research - Li, Jinquan (IntechOpen, 2017)
Rice provides staple food for more than 50% of the world's population and is an important crop in the world. With the new technologies such as high-throughput genome sequencing and integrated "-omis" methods applied in rice researches, great advancements have been made. This book was aimed to show a glance of new advancements in the international rice researches. The first section of the book introduced rice cultivation and production. As core sections of the book, the second and third sections introduced physiological and genetic mechanisms on grain quality and biotic and abiotic stress resistance as well as breeding. In the last section, we introduced new technologies such as chromatin immunoprecipitation, integrated "-omis" methods, and bistatic interferometry technology in rice research.